THE USE OF DRILLING METHOD IN TEACHING PHONETIC TRANSCRIPTION AND WORD STRESS OF PRONUNCIATION CLASS - Yudi Basuki (LinguA-LiterA: Journal of English Language Teaching Learning and Literature, 2018)
This research gives an account of how to enhance the students' phonetic transcription and word stress mastery of pronunciation through drilling method. That was obviously proved that the fourth-semester students' mastery of pronunciation was unsatisfactory. They were often found mispronounce English words. Meanwhile, phonetic transcription and word stress are considered as the main pronunciation features as a basis for having a good pronunciation. Then, drilling method was used in this research since it is an essential part of classroom pronunciation work and is also possibly the time in the lesson when the students are more reliant on the teacher. Besides, drilling is also fundamental to help students remember new items. However, this study was a classroom action research, which consisted of two cycles and each of cycles consisted of four phases. The second cycle was done based on the reflection in the first cycle by revising some drawbacks. The participants of the research were the fourth-semester students of English language education study program of STKIP PGRI Trenggalek. The data collection methods of this research had been obtained from pronunciation test and observation. Then, the data of this research were analyzed qualitatively and quantitatively. The research findings proved that the implementation of drilling method effectively enhanced the students‘ progressive achievement from the preliminary study to the first and the second cycle and to finally meet the success criteria toward learning outcome stated in the syllabus.